SIMULATION OF FREE ENERGY OF MIXING FOR A POLYMER SOLUTION USING A SPREADSHEET FOR LEARNING ACTIVITIES - Abu Yazid Raisal; Rosynanda Nur Fauziah; Heru Kuswanto (Jurnal Pendidikan Fisika, 2023)
Teaching physics is sometimes difficult to convey without using props or visualizations. Simulations can help teachers create and demonstrate real conditions in front of the class. In this article, we describe the usage of spreadsheets in simulating Gibbs free energy in mixing polymer solutions. We have created an model for the simulation consisting of a main spreadsheet and several secondary spreadsheets. A spreadsheet was chosen to simulate Gibbs free energy because spreadsheets can perform numerical representations in tables. This simple simulation can be used when discussing the topic of polymer thermodynamics. Teachers can start by deriving mathematical equations and then show simulations to visualize the equations. Another option is for students to be asked to create their simulations after deriving a mathematical equation. Using simulation in learning can make learning more interactive and help students understand material physics subjects more easily. Spreadsheets can be an alternative for teachers when explaining abstract material to students. Furthermore, simulations with spreadsheets can also support physics learning remotely.